Analysis of semiconductor materials and devices - Guo, Boyang. (2011)
Waveguide Photodetector (WGPD) has gathered increased attention due to the high demand in large bandwidth network capabilities as it is able to operate in a very wide range of frequencies. However, this leads to the problem of reflection which results in power loss during transfer. In order to minimize the effects of reflection, impedance matching has to be incorporated in the overall design of the system so as to achieve maximum power transfer. In this thesis, the experimental data of a 1.55 μm GaNAsSb/GaAs WGPD, with operating frequency ranging from 100MHz to 10GHz, is used to simulate the matching impedance circuit using the Advanced Design System (ADS) software. Background study will be done on the Smith chart and impedance matching. More emphasis will be placed on studying the concept of impedance matching, impedance matching techniques and return loss relation to impedance matching. The simulation will be divided into two parts. The first part will be designing a matching circuit for single frequency impedance matching. The second part will be a build-up of the single frequency matching circuit to design a impedance matching circuit for a wideband frequency range of 100MHz to 10GHz. Simulation will be done using the chosen impedance matching technique (L network) to verify the effectiveness of matching the input and output impedance. Simulation has shown that the chosen matching technique provides a good impedance matching for both the single frequency and the wideband frequency.